The Role of Peer Support in Managing Occupational Stress: A Qualitative Study of the Sustaining Resilience at Work Intervention. (February 2020) - Agarwal, Bhavya; Brooks, Samantha K.; Greenberg, Neil
Background: Peer support at work may support psychological resilience by enhancing coping skills and providing social support. The current study aimed to examine how a workplace peer support program, "Sustaining Resilience at Work" (StRaW), may support employee mental health from the perspective of the trained peer supporter. Method : Nine individuals from various public and private organizations who had completed StRaW peer supporter training participated in semi-structured interviews to explore their views on the StRaW program. Data were analyzed using inductive thematic analysis. Findings : Three main themes emerged: the impact of workplace stressors on employee mental health, the impact of StRaW, and feedback on StRaW. The results suggested positive effects of StRaW training on practitioners' ability to support colleagues and maintain their own psychological well-being. Discussion/Application to Practice : Our results indicated that peer support programs in the workplace may improve employees' well-being and relationships between employees. As such, occupational health professionals should recommend that their organizations invest in these types of programs to improve organizational resilience. They should encourage employees they consider to be capable of supporting their colleagues to undergo this training as evidence suggests this is beneficial to the trained employees' own well-being, rather than making them feel burdened or under pressure. Occupational health professionals should also view such programs as useful ways of improving attitudes toward mental health within their organizations.